Aqueous Biphasic Systems Composed of Ionic Liquids and Acetate-Based Salts: Phase Diagrams, Densities, and Viscosities - Quental, M.V. (American Chemical Society, 2015)
Ionic-liquid-based aqueous biphasic systems (IL-based ABS) have been largely investigated as promising extraction and purification routes. In this context, the determination of their phase diagrams and the physical properties of the coexisting phases are of high relevance when envisaging their large-scale applications. Low viscosities improve mass transfer and reduce energy consumption, while the knowledge of their densities is important for equipment design. In this work, novel phase diagrams for aqueous solutions of imidazolium-based ILs combined with acetate-based salts, namely KCH3CO2 or NaCH3CO2, are reported and discussed. The ability of the acetate-based salts to induce the phase separation not only depends on the ions hydration energy, but also on the concentration of "free" ions in solution. The tie-lines, tie-line lengths, and critical points are also addressed. Experimental measurements of density and viscosity of the coexisting phases, for the different systems and at several compositions and temperatures, are additionally presented. The Othmer-Tobias and Bancroft equations are also applied to ascertain the tie-lines coherence. It is here shown that low-viscous IL-based ABS, with a high difference in the densities of the coexisting phases, can be formed with organic and biodegradable salts thus offering enhanced features over conventional polymer-based systems. Â© 2015 American Chemical Society.